If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(4x + -7) + -2(3x + 4) + 10 = 3(3x + -5) + -43 Reorder the terms: 5(-7 + 4x) + -2(3x + 4) + 10 = 3(3x + -5) + -43 (-7 * 5 + 4x * 5) + -2(3x + 4) + 10 = 3(3x + -5) + -43 (-35 + 20x) + -2(3x + 4) + 10 = 3(3x + -5) + -43 Reorder the terms: -35 + 20x + -2(4 + 3x) + 10 = 3(3x + -5) + -43 -35 + 20x + (4 * -2 + 3x * -2) + 10 = 3(3x + -5) + -43 -35 + 20x + (-8 + -6x) + 10 = 3(3x + -5) + -43 Reorder the terms: -35 + -8 + 10 + 20x + -6x = 3(3x + -5) + -43 Combine like terms: -35 + -8 = -43 -43 + 10 + 20x + -6x = 3(3x + -5) + -43 Combine like terms: -43 + 10 = -33 -33 + 20x + -6x = 3(3x + -5) + -43 Combine like terms: 20x + -6x = 14x -33 + 14x = 3(3x + -5) + -43 Reorder the terms: -33 + 14x = 3(-5 + 3x) + -43 -33 + 14x = (-5 * 3 + 3x * 3) + -43 -33 + 14x = (-15 + 9x) + -43 Reorder the terms: -33 + 14x = -15 + -43 + 9x Combine like terms: -15 + -43 = -58 -33 + 14x = -58 + 9x Solving -33 + 14x = -58 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -33 + 14x + -9x = -58 + 9x + -9x Combine like terms: 14x + -9x = 5x -33 + 5x = -58 + 9x + -9x Combine like terms: 9x + -9x = 0 -33 + 5x = -58 + 0 -33 + 5x = -58 Add '33' to each side of the equation. -33 + 33 + 5x = -58 + 33 Combine like terms: -33 + 33 = 0 0 + 5x = -58 + 33 5x = -58 + 33 Combine like terms: -58 + 33 = -25 5x = -25 Divide each side by '5'. x = -5 Simplifying x = -5
| 3x-(x+5)= | | 8x+12y=15 | | x^2-(a+b)x-ab= | | 6x^2-48x+96=300 | | 160,000/1/3 | | 6x^2-396=0 | | {4^31)-1}/{(4^3)-1)} | | 6x^2-96=300 | | 1-3(x+4)=2(x-1) | | e^((1/7)lnx) | | 7ab=4*ba | | 6p+169=324 | | g(x)=1/6f(x) | | g(x)=2/3f(x) | | 5-29=4z | | 3.4x=-6.6 | | 4w+6=4(w+3)-13 | | 5z^2+12z+7= | | 3x-4x^2=-25 | | 4(n+5)-5(2n-1)=n-24 | | 2(cosx)^3-cosx-(√3/4)=0 | | 8a+1+25=356 | | 8a+1+25=35635 | | 6x^8z^3+48x^5=0 | | 4x=-15y-17 | | 4x=-15-17 | | 7a/2=5a-3 | | 15*12-16*N=967 | | -2.2+(-1.9)= | | R=9 | | 6(v)=6v+15 | | Y+y-10y+21=0 |